Meiosis and pollen viability of Brazil Nut Tree (Bertholletia excelsa Bonpl.) (Research, Society and Development, 2022)
The Brazil nut tree (Bertholletia excelsa Bonpl.) is one of the most important tree species in the Amazon Forest. Reproductive phenology studies help in the development of manual and natural pollination strategies. Pollination is one of the ways to ensure the species survival through the ovule fertilization by the pollen grain. This work aimed to characterize the meiotic behavior, estimate pollen viability and determine the pollen grains reserve content in B. excelsa native in Mato Grosso Amazon. Flower buds were collected at various stages of development in a population, and then they were fixed in a acetic acid solution 3:1 and 70% alcohol. For meiotic analysis, acetic carmine dye was used, for pollen viability, acetic carmine and Alexander's reactive dyes and for cytochemistry, lugol and sudan IV dyes. All observations were performed under an optical microscope. It was observed that the species has 2n=2x=26 chromosomes. Meiosis was considered regular, with a meiotic index of 92.4%, with some latent chromosomes being observed in anaphase I, in addition to irregular segregation of chromosomes and cellular dyssynchrony in anaphase II. Pollen viability through dyes was considered high, above 80%, along with viability through pollen tube germination, which was above 50% in the best culture medium. Cytochemical analysis revealed positivity for starches and lipids, with a higher percentage of lipids. The Brazil nut tree has regular meiosis, high pollen viability and a higher percentage of lipids in its pollen grains.